Carmen [videorecording (DVD)] - Buhagiar, Valerie; McElhone, Natascha, 1969-; Love, Steven; Clarkin, Richard (Good Deed Entertainment, 2022)
In a small Mediterranean village, Carmen has looked after her brother, the local priest, her entire life. After he dies Carmen begins to see the world, and herself, in a new light.